Beyond Western-Oriented Communication Theories: A Normative Arab-Islamic Perspective - Ayish, Muhammad (Javnost-The Public, 2003)
For many decades, communication as a theoretical field of study has been dominated by Western-oriented perspectives that arose in the context of media perceptions in Western Europe and North America. Western communication theories have been promoted around the world as possessing a strong element of universalism. In recent years, this approach has been challenged on the basis of obfuscating the cultural peculiarities of non-Western societies as significant components of communication theorization. In this article, the author presents a normative Arab-Islamic perspective as a basis for future communication theory building in the Arab-Islamic context. Drawing on the notion of “Worldview,” the Arab-Islamic perspective identifies four antithetical conceptual constructs that bear on the nature of communication: individualism-conformity, transcendentalism-existentialism, intuitive-rational processes, and egalitarianism-hierarchy. The author concludes that Arab-Islamic communication patterns are formalistic, indirect, hyperbolic, asymmetrical, metaphysical and orally biased.